Investigations of the Oral Health Status of a Group of Libyan Children and Its Relation to Home Care - Musrati, Ahmed; M. Ali , Fowziya; Huew, Rasmia; Herwis, Khadija; H. Mohamed , Fathia (Libyan Journal of Dentistry, 2017)
The aim: this study was aimed to investigate the oral health status of a group of Libyan children. Subjects and Methods: Two hundred and eight children were included in the study. The samples were subdivided into 3 age groups (6, 6-12 and >12 years old). Both the extent and the degree of gingivitis severity were assessed in the incisor area of the maxilla and the incisor and canine area of the mandible in the anterior teeth by using extent of gingivitis (GE) and gingivitis severity (GS) indices. The individual gingival units: papillae (P), Margins (M) and attached gingivae (A) were assessed for the presence of inflammation based on visual examinations. The caries experience was assessed by using dmft for deciduous teeth and DMFT for permanent teeth. Results: EG & GS were assessed and the majority (206 out of 208 i.e. 99%) of children suffered from different degrees of gingival inflammation. Untreated carious lesions were noticed in 194 (93%) of cases in this group. Conclusion: There has been more untreated caries and more pronounced gingival inflammations of various degrees in this sample due to the lack of proper dental care.